2016
DOI: 10.1097/md.0000000000003299
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Korean Male Breast Cancer Using an Online Nationwide Breast-Cancer Database

Abstract: The aim of this study is to review the characteristics and the survival rate in male breast cancer (MBC) patients in Korea over a 31-year period. Additionally, we analyzed the overall survival (OS) rate of a group of MBC matched to females with breast cancer.We retrospectively analyzed the data from 400 Korean patients who were treated for MBC from 1978 to 2009. Patient demographics and clinical information were routinely documented throughout the study period. Survival and prognostic factors were evaluated. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
5
27
1
Order By: Relevance
“…Relative to FBC, adjuvant radiotherapy is less commonly performed for MBC patients [17], and we also found that radiotherapy was significantly less likely to be performed for MBC than for FBC. Considering the patterns of cancer in men and women according to stage, radiotherapy was performed significantly less frequently in MBC overall, and within each stage (S1 Table).…”
Section: Discussionmentioning
confidence: 57%
“…Relative to FBC, adjuvant radiotherapy is less commonly performed for MBC patients [17], and we also found that radiotherapy was significantly less likely to be performed for MBC than for FBC. Considering the patterns of cancer in men and women according to stage, radiotherapy was performed significantly less frequently in MBC overall, and within each stage (S1 Table).…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we used data approved by the Korean Breast Cancer Society registration system (KBCR). Since 1996, the KBCR has been registering cases submitted by breast surgeons at 110 training hospitals nationwide [ 2 14 15 ]. The cause and date of death in the data were used in connection with the Korea Central Cancer Registration Data of the Ministry of Health and Welfare in collaboration with the Korean National Statistical Office to compile complete death statistics which were updated through 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to female breast cancer, male breast cancer accounts for less than 1% of all breast cancers in the United States [7] and Korea [8]. Male breast cancer was diagnosed at early stages and high rate of ER positivity [8], but evidences revealed that aromatase inhibitors are less effective in males than in post-menopausal women [9].…”
Section: Introductionmentioning
confidence: 99%
“…Male breast cancer was diagnosed at early stages and high rate of ER positivity [8], but evidences revealed that aromatase inhibitors are less effective in males than in post-menopausal women [9]. Though most male breast cancer subtypes are invasive ductal carcinomas, the 5-year overall survival rate was comparable between male and female breast cancer patients in Korea [8] while poorer overall survival but better breast cancer-specific survival in Hong Kong [10]. In our NHI database, the incidence of male breast cancer was rare, accounted for 0.4% of all breast cancer (see Supplementary Table 1).…”
Section: Introductionmentioning
confidence: 99%